Communication Patterns within Indonesia's Religious Moderation Index: An Analysis through Habermas's Theory of Communicative Action: (Communication Patterns in the Religious Moderation Index in Indonesia) - Faza, M. Nabil Hasan; Hanurrahman, Muh.Gilang; Bakhri, Syahrul; Susanti, Selvia Dwi; Ali, M. Khaidar (Prodi Sosiologi Agama, 2025)
This study explores the patterns of communication in religious moderation in Indonesia as a strategic approach to maintaining interreligious harmony and coexistence in a pluralistic society. Using a descriptive qualitative method and a critical review of the Ministry of Religious Affairs’ policies, supported by Habermas's theory of communicative action, this research identifies four key communication patterns: dialogical, educational, interpersonal, and media-based communication. Each pattern plays a vital role in promoting understanding, tolerance, and national commitment—core indicators of religious moderation. The study also highlights the significance of external factors such as education, media, and public policy in reinforcing inclusive and effective communication. Moreover, it emphasizes the need for further empirical and interdisciplinary research to better understand the dynamics of interreligious communication. The findings of this study aim to contribute to public policy development and to strengthen sustainable practices of religious moderation in Indonesia